Combinatorial optimization of synthetic operons for the microbial production of p-coumaryl alcohol with Escherichia coli. Issue 1 (December 2015) - van Summeren-Wesenhagen, Philana; Voges, Raphael; Dennig, Alexander; Sokolowsky, Sascha; Noack, Stephan; Schwaneberg, Ulrich; Marienhagen, Jan
Abstract Background Microbes are extensively engineered to produce compounds of biotechnological or pharmaceutical interest. However, functional integration of synthetic pathways into the respective host cell metabolism and optimization of heterologous gene expression for achieving high product titers is still a challenging task. In this manuscript, we describe the optimization of a tetracistronic operon for the microbial production of the plant-derived phenylpropanoidp -coumaryl alcohol inEscherichia coli . Results Basis for the construction of ap -coumaryl alcohol producing strain was the development of Operon-PLICing as method for the rapid combinatorial assembly of synthetic operons. This method is based on the chemical cleavage reaction of phosphorothioate bonds in an iodine/ethanol solution to generate complementary, single-stranded overhangs and subsequent hybridization of multiple DNA-fragments. Furthermore, during the assembly of these DNA-fragments, Operon-PLICing offers the opportunity for balancing gene expression of all pathway genes on the level of translation for maximizing product titers by varying the spacing between the Shine-Dalgarno sequence and START codon. With Operon-PLICing, 81 different clones, each one carrying a differentp -coumaryl alcohol operon, were individually constructed and screened forp -coumaryl alcohol formation within a few days. The absolute product titer of the best five variants ranged from 48 to 52 mg/Lp -coumaryl alcohol without any further optimization of growth and production conditions. Conclusions Operon-PLICing is sequence-independent and thus does not require any specific recognition or target sequences for enzymatic activities since all hybridization sites can be arbitrarily selected. In fact, after PCR-amplification, no endonucleases or ligases, frequently used in other methods, are needed. The modularity, simplicity and robustness of Operon-PLICing would be perfectly suited for an automation of cloning in the microtiter plate format.